2019
DOI: 10.1007/s42452-019-0424-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic capping agents on the optical and photocatalytic activity of mesoporous TiO2 nanoparticles by sol–gel method

Abstract: In this work, the effect of capping agent effects on the structural, morphological, optical properties and photocatalytic removal of Rhodamine B (RhB) dye has been investigated. TiO 2 nanoparticles were synthesized by a simple, fast and ecofriendly sol-gel method, in the presence of various capping agents, including ethylenediamine, polyvinyl alcohol (PVA), ethylene glycol, glucose and valine. The obtained TiO 2 nanoparticles have been characterized by X-ray diffraction (XRD), energy dispersive X-ray analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Among them, TiO 2 NPs are a well-known semiconductor with a wide bandgap of 3.2 eV for anatase and 3.0 eV for rutile phase [9], but the brookite phase is rare to obtain [10]. The Anatase and rutile phase of TiO 2 exhibits a tetragonal crystal structure, but the brookite phase is an orthorhombic structure [11]. The transition metal oxide, mainly TiO 2 , is widely used in cosmetics, photocatalysts, medicines, sensors, and solar cell applications because of its peculiar properties like interconnected pores and large surface area [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TiO 2 NPs are a well-known semiconductor with a wide bandgap of 3.2 eV for anatase and 3.0 eV for rutile phase [9], but the brookite phase is rare to obtain [10]. The Anatase and rutile phase of TiO 2 exhibits a tetragonal crystal structure, but the brookite phase is an orthorhombic structure [11]. The transition metal oxide, mainly TiO 2 , is widely used in cosmetics, photocatalysts, medicines, sensors, and solar cell applications because of its peculiar properties like interconnected pores and large surface area [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that reduced agglomeration of nanoparticles increases the accessible surface area on the material, which could lead to an increase in their photocatalytic efficiency [ 36 ]. Other studies have shown that if the surface morphology of nanoparticles is rough, it enhances the photocatalytic degradation efficiency of the material [ 37 , 38 ]. TOPO-PbS1 shows a flaky surface morphology while the TOPO-PbS2 SEM image reveals a closely packed spherical surface morphology.…”
Section: Resultsmentioning
confidence: 99%
“…45,52 The finally heated and dried have the possibility to give us metal oxide in a form of bulk materials, nanoparticles, or oxygen vacancy based on the heat-treatment process done. 28 A variety of metal oxide nanoparticles such as ZnO, 53 TiO 2 , 54 MgO, 55 ZrO 2 , 56 CuO, 57 and Nb 2 O 5 /SiO 2 (ref. 58) were synthesized by the sol–gel process.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%